Growth, Physiological, and Photosynthetic Responses of Xanthoceras sorbifolium Bunge Seedlings Under Various Degrees of Salinity - Zong, Jian-Wei; Zhang, Zhi-Long; Huang, Pei-Lu; Chen, Nai-Yu; Xue, Ke-Xin; Tian, Zhi-Yong; Yang, Yu-Hua (Frontiers in Plant Science, 2021)
Xanthoceras sorbifolium Bunge is priced for its medical and energetic values. The species also plays a key role in stabilizing ecologically fragile areas exposed to excess soil salinity. In this study, the effects of salinity on the growth, physiological, and photosynthetic parameters of X. sorbifolium Bunge were investigated. The X. sorbifolium seedlings were subjected to five salt treatments: 0 (control, CK), 70, 140, 210, and 280 mM of sodium chloride (NaCl) solutions. NaCl caused a decrease in plant height, specific leaf area, biomass, and root parameters. Leaf wilting and shedding and changes in root morphology, such as root length, root surface area, and root tips were observed. This study found that X. sorbifolium is tolerant to high salinity. Compared with the CK group, even if the concentration of NaCl was higher than 210 mM, the increase of the relative conductivity was also slow, while intercellular CO2 concentration had a similar trend. Moreover, NaCl stress caused an increase in the malondialdehyde (MDA), soluble proteins, and proline. Among the enzymes in the plant, the catalase (CAT) activity increases first and decreased with the increase in the intensity of NaCl stress, but the salt treatment had no significant effect on superoxide dismutase (SOD) activity. The peroxidase (POD) showed an increasing trend under salt stress. It was found that the photosynthesis of X. sorbifolium was notably impacted by saline stress. NaCl toxicity induced a noticeable influence on leaf net photosynthetic rate (Pn), stomatal conductance (Gs), intercellular CO2 concentration (Ci), transpiration rate (E), and water use efficiency (Wue). As salt concentration increased, the content of chlorophyll decreased. It can be found that a low concentration of NaCl induced the increase of photosynthetic capacity but a high-intensity exposure to stress resulted in the reduction of photosynthetic efficiency and SOD activity, which had a positive correlation. In summary, salt-induced ionic stress primarily controlled root morphology, osmotic adjustment, and enzyme activities of salt-treated X. sorbifolium leaves, whereas the low salt load could, in fact, promote the growth of roots.